Evaluating agripreneurs' satisfaction: Exploring the effect of demographics and emporographics - G. Yoganandan; Abdul Aziz Abdul Rahman; M. Vasan; Abdelrhman Meero (Journal of Innovation and Entrepreneurship, 2022)
This paper attempts to gauge the satisfaction of agripreneurs and seeks to explore the effect of demographics and emporographics on the agripreneurs' satisfaction. This study proposes a seven-dimension survey instrument, called AprenSAT, for measuring agripreneurs' satisfaction. Responses from 784 agripreneurs are analyzed by applying exploratory and confirmatory factor analysis and multiple linear regression. The extraction of seven factors confirms that agripreneurs' satisfaction is influenced by material availability, government support, farm growth, farm income, market performance, cultivation & production and perceived farm image. The linear regression result delineates that demographic factors such as age, education level and farming experience significantly influence the agripreneurs' satisfaction. Similarly, variables of emporographics such as farm age, farm size, annual income, land ownership, sources of funds, and intercropping have a substantial influence on agripreneurs' satisfaction. We recommend information dissemination, hands-on training, the creation of adequate infrastructure and technology adoption to enhance agripreneurs' satisfaction and rural development.
Keywords: 650; Agribusiness; Agricultural entrepreneurship; Agripreneurs; Agripreneurship; Demographics; Emporographics; Rural Farmers